Dampak Pendekatan Pembelajaran Kolaboratif terhadap Keterampilan Sosial Siswa : Studi Pustaka - Khansa Labibah; Marsofiyati Marsofiyati (Pusat Riset dan Inovasi Nasional, 2025)
This study analyzes the impact of collaborative learning approaches on students' social skills through a literature review method. The research is grounded in the importance of social skills for students' future social and professional lives, encompassing communication, teamwork, and empathy. Collaborative learning, supported by Vygotsky's Zone of Proximal Development theory and Bandura's social learning theory, emphasizes social interaction in education. The findings reveal that collaborative learning significantly enhances students' social skills, including communication, teamwork, and critical thinking, through models like the Teams Games Tournament (TGT). However, challenges such as unequal student participation and complex group dynamics remain obstacles to be addressed. These findings provide critical implications for educators in designing effective learning strategies and emphasize the necessity of teacher training to manage collaborative learning successfully across different educational levels.